Pakistan, Islamisation, army and foreign policy - Chengappa, Bidanda M. (New Delhi : A.P.H. Pub. Corp., 2004)
Includes interviews.
Includes index.
Keywords: Islam and state -- Pakistan; Pakistan -- Politics and government -- 1971-1988.; Pakistan -- Politics and government -- 1988-; Pakistan -- Foreign relations -- India; India -- Foreign relations -- Pakistan